Le Tailleur d'Inversness - Zajac, Matthew (Annales littéraires, 2020)
The journey of Mateusz Zajac, born in Galicia (Poland) in 1919, where he lived until his mobilization during the Second World War, has the appearance of a Homeric epic. Due to the complex geopolitical historical context, like many of his fellow human beings, the young man is uprooted and thrown on the roads to fight under different flags, in armies of different nations, according to the victories and defeats that are remodelling this part of Eastern Europe. Survival is heroic. In The Tailor of Inverness, the pride and love of his son Matthew, a modest author, emerge at every turn of a dramatic and theatrical story where the unimaginable is experienced.